Family shapes microbiome differences in Oklahoma salamanders - Kirsch, Madelyn R.; Smith, Sierra N.; Becker, Daniel J.; Watters, Jessa L.; Marske, Katharine A.; Siler, Cameron D.; Lanier, Hayley C. (Frontiers in Microbiomes, 2024)
Given the role of microbiomes in promoting host health and homeostasis, understanding the factors shaping skin microbial communities in wild vertebrates has become increasingly important in conservation. This goal is even more pressing for amphibians, for which the skin has multiple critical functions, and pathogens currently decimating populations are linked to significant changes in skin microbiomes. However, because microbiomes are also shaped by environmental and ecological influences, as well as by host phylogeny, it is important to quantify these contributions to microbiome structure in the presence of infection. To understand the joint influence of these diverse factors shaping microbiomes, we used 16S rRNA sequencing to characterize the skin microbial communities of six salamander species (families Plethodontidae and Salamandridae) found in Oklahoma and contrasted the effects of infection status, phylogeny, host ecology, and host environment (i.e., climate) on skin microbiomes. Differences at the level of host family were the main factor influencing microbiome diversity; however, we did not detect a substantial phylogenetic signal. Instead, host ecology and environment were more important in driving microbiome differences among species and genera. Salamanders that tested positive for the skin fungal parasite Batrachochytrium dendrobatidis (Bd) also had slightly less diverse microbiomes than Bd-free animals, but no such differences were associated with the systemic pathogen ranavirus (RV). Together, these results indicate a nuanced relationship between the number and type of microbes present on the skin and the factors influencing them. By developing a baseline assessment of the microbiome diversity and richness present on the skin of these focal species, this work also provides a foundation for monitoring and evaluating changes in skin microbiomes as populations continue to experience stressors and diseases.